Patient satisfaction- comparison of the comprehensive care model with traditional model of delivering dental services in Tehran University of Medical Sciences - Afsaneh Pakdaman; Ahmad Khormali; Ahmad Reza Shamshiri (Tehran University of Medical Sciences, 2013)
Background and Aims: One of the important aspects for evaluating an organization is assessing the level of satisfaction of the clients. This study was conducted to compare the level of satisfaction between traditional and new methods of delivering dental care in the clinic of Tehran University of Medical Sciences.   Materials and Methods: A cross-sectional study was conducted on 308 patients received dental care at the dental clinics of Tehran University of Medical Sciences in spring 2010. Data were collected from Comprehensive Care Unit (CCU) in addition to 7 isolated clinics including restorative, periodontics, endodontics, radiology, and prosthodontics (fix and removable) using translated version of the Dental Satisfaction Questionnaire (DSQ), consisted of 19 questions in three main domains in addition to demographic questions. Descriptive statistics was used as percentage of answers. In order to compare the mean score between domains ANOVA test was used.   Results: The standardized mean scores in each domain were: pain control 58±17, access 59±12, quality 68±11 and total Dental Satisfaction Index (DSI) score of 62±10. 92.5% of the respondents reported that students were very careful when examining their patients. 96.8% reported that they treat their patients with respect . The most common reasons for dissatisfaction apart from waiting time and getting appointments were not providing preventive care and pain control.   Conclusion: The results of this study shows acceptable level of satisfaction with dental care in teaching clinics of this dental school, however efforts on implementing preventive care and pain control strategies are suggested.